Longitudinal evaluation of the relationship between maladaptive trauma coping and distress: examination following the mass shooting at Virginia Tech - Littleton, Heather (2011)
Growing evidence supports that the coping strategies that individuals utilize are a key predictor of distress following trauma. However, there is limited longitudinal research examining the relationship between psychological distress and coping over time, and even less research examining the possibility of reciprocal relationships between distress and coping, despite the fact that prior theoretical work posits such a relationship. The current study modeled the relationship between distress (PTSD and general distress) and maladaptive coping over time in a sample of 368 college women exposed to the mass shooting at Virginia Tech (VT). Participants completed web surveys regarding their distress, shooting-related coping, and shooting-related PTSD 2 months, 6 months, and 1 year following the shooting. They also completed measures of their psychological distress prior to the shooting as part of an unrelated study. A structural cross-lagged model with latent variables supported a reciprocal relationship between maladaptive coping and general psychological distress over time. In contrast, the cross-lagged model evaluating the relationship between PTSD and maladaptive coping supported that PTSD symptoms predicted coping over time, but there was no reciprocal relationship between coping and PTSD. Implications of the findings for future work examining adjustment following traumatic events are discussed.